Employee Perception of the Effectiveness of the Warehouses: With Especial Reference to the Telecommunication Infrastructure Development Field, Sri Lanka - Rathnayake JA; Karunarathne EACP (International Journal of Management, Accounting and Economics, 2015)
Warehouse plays a major role in logistic operations especially in the telecommunication infrastructure development industry. Inefficient warehouse management makes huge cost to the company. Thus, it is important to manage warehouses especially in this industry as they are using very specific materials, machineries, equipment and tools. On the other hand, firms need to keep larger as well as costly inventories for the successful completion of the construction projects. This implies the differences with compared to other type of warehouses and also generates some specific requirements in warehousing for this industry. Thus, this research study focuses to identify and examine the factors affecting effectiveness of warehouses in telecommunication infrastructure construction industry. The study was carried out by performing a comprehensive survey and a questionnaire was used to get the feedback from the selected sample which comprises both executive and non-executive employees work in warehouses. For the purpose of analysis, descriptive statistics and other statistical tools were used to examine the factors. Through the study, environmental impacts, emergency unloading and safety & protection were identified as largely affecting factors to the warehouse effectiveness and their behaviours were further examined. Based on findings, the paper has given recommendations for telecommunication infrastructure construction firms to effectively manage their warehouses for the better performance in their construction projects.